The application of magnetic resonance fingerprinting to single voxel proton spectroscopy. (3rd September 2018) - Kulpanovich, Alexey; Tal, Assaf
Abstract : Magnetic resonance fingerprinting has been proposed as a method for undersampling k ‐space while simultaneously yielding multiparametric tissue maps. In the context of single voxel spectroscopy, fingerprinting can provide a unified framework for parameter estimation. We demonstrate the utility of such a magnetic resonance spectroscopic fingerprinting (MRSF) framework for simultaneously quantifying metabolite concentrations, T 1 and T 2 relaxation times and transmit inhomogeneity for major singlets of N‐acetylaspartate, creatine and choline. This is achieved by varying T R, T E and the flip angle of the first pulse in a PRESS sequence between successive excitations (i.e. successive T R values). The need for multiparametric schemes such as MRSF for accurate medical diagnostics is demonstrated with the aid of realistic in vivo simulations; these show that certain schemes lead to substantial increases to the area under receiver operating characteristics of metabolite concentrations, when viewed as classifiers of pathologies. Numerical simulations and phantom and in vivo experiments using several different schedules of variable length demonstrate superior precision and accuracy for metabolite concentrations and longitudinal relaxation, and similar performance for the quantification of transverse relaxation. Abstract : Magnetic resonance fingerprinting (MRF) is capable of yielding multiparametric tissue maps, and in the context of proton single voxel spectroscopy ( 1 H‐MRS) can provide a unified framework for parameter estimation. We demonstrate the utility of such a spectroscopic MRF framework for simultaneously quantifying metabolite concentrations, T1 and T2 relaxation times and transmit (B1+ ) inhomogeneity for major singlets in the human brain. Results demonstrate superior precision and accuracy for metabolite concentrations and longitudinal relaxation over the conventional measurement methods.